Liquid Biopsy in Advanced Colorectal Cancer: Clinical Applications of Different Analytes - Marco Donatello Delcuratolo; Andrea Modrego-Sánchez; Maristella Bungaro; Beatriz Antón-Pascual; Santiago Teran; Valentina Dipace; Silvia Novello; Rocio Garcia-Carbonero; Francesco Passiglia; Cristina Graválos-Castro (MDPI AG, 2023)
Colorectal cancer is one of the most prevalent cancers nowadays. In the metastatic setting, diagnosis and treatment have relied on tumor tissue analysis. However, the different limitations of this approach have recently opened the door to the introduction of liquid biopsy in the clinical setting. Liquid biopsy provides real-time information about the tumor and its heterogeneity in a simple, non-invasive, and repeatable way. There are several analytes that can be sought: exosomes, circulating tumor cells, and circulating tumor DNA, showing promising results in the areas of early detection, minimal residual disease, prognosis, or response to treatment. Here, we review the clinical applications of liquid biopsy in advanced colorectal cancer patients, focusing on metastatic diagnosis, prognostic assessment, drug sensitivity, treatment response, and acquired resistance monitoring.